OPTIMIZING SERVICE QUALITY MANAGEMENT FOR ENHANCED USER SATISFACTION IN TIN CAN ISLAND PORT, LAGOS (Journal of the Management Sciences, 2025)
Poor Service quality in Nigerian seaports is worrisome because majority of the cargo that are meant for Nigerian seaports are being diverted to the neighboring seaports leading to loss of revenue to the government. This research aim to optimize service quality management in Tin Can Island Port, Lagos, Nigeria. The objectives of this study were to assess the impact of tangibility and reliability on port user satisfaction. Survey type of descriptive research design was utilized. The population consist of eight hundred and twenty (820) respondents. (269) two hundred and sixty-nine respondents made up the sample surveyed in this study; this was derived with Taro-Yamane (1967) formula. The study used simple random sampling criteria to choose the respondents. Questionnaire was the only instrument adopted to collect data. Simple percentage, frequency and Pearson’s correlation were used to analyze data and hypothesis tested with multiple regression analysis. The study findings revealed that tangibility and reliability positively affect port user satisfaction. The research concludes that effective service quality will enhance port users’ satisfaction. Hence, the research recommends that government and individuals’ terminal operators are encouraged to provide up-to-date facilities and equipment. Secondly, officials at the seaports should always show concern and support port users whenever the need arises.
Keywords: Enhanced; Optimization; Reliability; Service Quality Management; Tangibility; User satisfaction